Climate Change Disclosure and Firm Value: The Moderating Role of Environmental Performance - Auliya Zulfatillah; Alifa Wahyu Wulan Agustin (International Economic Conference of Business and Accounting, 2025)
This study investigates the influence of climate change disclosure on firm value, with environmental performance as a moderating variable. The sample consists of 63 industrial sector companies listed on the Indonesia Stock Exchange during 2021–2023. Climate change disclosure is measured using indicators adapted from the Task Force on Climate-Related Financial Disclosure (TCFD). Data were collected from annual reports, sustainability reports, and PROPER ratings, and analyzed using Moderated Regression Analysis (MRA). The findings reveal that climate change disclosure has a negative effect on firm value, indicating that disclosure alone may raise investor concerns by exposing risks, compliance costs, or environmental liabilities. However, environmental performance significantly and positively moderates this relationship, reducing the negative effect of disclosure. These results highlight that disclosure, when supported by strong environmental performance, serves as a credible signal of accountability and resilience, thereby improving firms’ market perception of sustainability practices.